2014
DOI: 10.1038/pr.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

Impact of levosimendan on brain injury patterns in a lamb model of infant cardiopulmonary bypass

Abstract: Background:The effects of levosimendan (Levo) on injury patterns in the immature brain following cardiopulmonary bypass (CPB) are unknown. Methods: Eighteen 3-to 4-wk-old anesthetized lambs, instrumented with vascular catheters and aortic and right carotid artery flow probes, were allocated to non-CPB, CPB, or CPB+Levo groups (each n = 6). After 120 min CPB with 90 min aortic cross-clamp, CPB animals received dopamine, and CPB+Levo animals both dopamine and Levo, for 4 h. All lambs then underwent brain magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Moreover, a recent report showed that levosimendan was beneficial in a model of injury to the immature brain following cardiopulmonary bypass (Namachivayam et al, 2014). Finally, Varvarousi et al (2014) described positive effects of levosimendan in post-cardiac arrest brain injury, and Bleilevens et al (2014) showed that levosimendan treatment significantly reduces cerebral infarct size in the cortex in a rat model.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a recent report showed that levosimendan was beneficial in a model of injury to the immature brain following cardiopulmonary bypass (Namachivayam et al, 2014). Finally, Varvarousi et al (2014) described positive effects of levosimendan in post-cardiac arrest brain injury, and Bleilevens et al (2014) showed that levosimendan treatment significantly reduces cerebral infarct size in the cortex in a rat model.…”
Section: Discussionmentioning
confidence: 98%
“…Plusieurs travaux se sont intéressés aux propriétés neuroprotectrices du levosimendan. Chez des agneaux ayant subit un clampage aortique de 90 minutes sous CEC, le levosimendan, en augmentant le débit dans les artères carotides, était responsable d'une baisse significative des marqueurs de stress oxydatif dans le cerveau, confirmant ainsi son potentiel neuroprotecteur dans le cadre d'une chirurgie cardiaque [59]. Une étude récente, réalisée chez le rat, a donné des résultats spectaculaires et encourageants pour le traitement des lésions cérébrales ischémiques.…”
Section: Perspectivesunclassified
“…Anesthesia, surgical preparation, cardiovascular instrumentation, and physiological measurements were performed as detailed in the Appendix and according to our previous work [5,10,11].…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
“…The infant CPB circuit details are presented in the Appendix, as previously reported [11]. After CPB was instituted, the ascending aorta was cross-clamped, and induction blood cardioplegia was infused over 3 minutes through a cannula inserted proximal to the cross-clamp to arrest the heart.…”
Section: Experimental Protocolmentioning
confidence: 99%